Model-based patterns in stomach cancer mortality worldwide - Peleteiro, B (2014)
The decrease in stomach cancer mortality was not because of specific interventions, and is likely that different countries follow a similar model of variation. Here, we aimed to identify model-based patterns in the time trends of stomach cancer mortality worldwide. Stomach cancer mortality rates were retrieved for 62 countries from the WHO mortality database. Sex-specific mixed models were used to describe time trends in age-standardized rates between 1980 and 2010 (age group 35-74 years; World standard population). Three patterns, similar for men and women, were identified through model-based clustering. Pattern 1 presented the highest mortality rates in 1980 (median: men, 81.5/100 000; women, 34.4/100 000) and pattern 3 the lowest ones (median: men, 24.4/100 000; women, 12.4/100 000). The decrease in mortality rates was greater in 1980-1995 than during 1996-2010. Assuming that the patterns characterized by the highest rates precede temporally those with lower mortality, the overlap of model predictions supports a 20-year lag between adjacent patterns. We propose a model for the variation in stomach cancer mortality with three stages that develop sequentially through a period of ∼70 years. The countries with the lowest mortality had the highest proportional decrease in mortality rates.